2016
DOI: 10.1111/pcn.12401
|View full text |Cite
|
Sign up to set email alerts
|

Goal‐directed behaviors in patients with schizophrenia: Concept relevance and updated model

Abstract: Goal-directed behaviors are formulated to pursue a given objective by constructing a plan and selecting actions that lead to the intended goal, either immediately or over an extended period. This concept is important to the study of human behavior because of its involvement in the majority of complex or novel situations that an individual may encounter, regardless of the cognitive, affective, or social abilities required. In this paper, we aim to demonstrate the relevance of goal-directed behaviors to our unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
0
10
0
9
Order By: Relevance
“…Emerging evidence suggests that motivation could mediate the relationship between neurocognition and both functional outcomes and quality of life in schizophrenia (Nakagami, Xie, Hoe, & Brekke, 2008). Though little data have focused on the relationships of neurocognition, motivation and self‐management, the cognitive mechanism involving goals and efforts selection is of great importance for action, as Rinaldi and Lefebvre (2016) referred in the framework of goal‐directed behaviours in schizophrenia. Recently, Thomas, Luther, Zullo, Beck, and Grant (2017) identified motivation as one of the key factors in the chain from neurocognition to community participation, in which self‐care activities were involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that motivation could mediate the relationship between neurocognition and both functional outcomes and quality of life in schizophrenia (Nakagami, Xie, Hoe, & Brekke, 2008). Though little data have focused on the relationships of neurocognition, motivation and self‐management, the cognitive mechanism involving goals and efforts selection is of great importance for action, as Rinaldi and Lefebvre (2016) referred in the framework of goal‐directed behaviours in schizophrenia. Recently, Thomas, Luther, Zullo, Beck, and Grant (2017) identified motivation as one of the key factors in the chain from neurocognition to community participation, in which self‐care activities were involved.…”
Section: Discussionmentioning
confidence: 99%
“…(Jochems, Duivenvoorden, van Dam, van der Feltz‐Cornelis, & Mulder, 2017). Self‐management in schizophrenia involves a wide range of goal‐directed and effortful activities that are relatively hard for patients to incorporate into everyday life, and motivation is the force that initiates and maintains such behaviours (Rinaldi & Lefebvre, 2016). Recent data have further suggested that motivation may mediate the impact of neurocognitive impairment on personal care and interpersonal skills, independent living skills, social functions and quality of life (Bowie et al., 2008; Cardenas et al., 2013; Chang et al., 2017; Harvey & Strassnig, 2012; Quinlan, Roesch, & Granholm, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have proposed models for how goal-directed behavior is impacted in schizophrenia (Frith, 2000). One model in particular suggests that negative symptoms are associated with a deficit in action initiation and positive symptoms are associated with deficits in cognitive control, with disorganized symptoms associated with deficits in contextual information integration (Rinaldi and Lefebvre, 2016). In a study investigating goal-directed planning and action in a virtual environment, impairments in these processes were observed in those with schizophrenia (Siddiqui et al, 2019).…”
Section: Goal-directed Behavior In Schizophreniamentioning
confidence: 99%
“…Ce modèle est entre autres issu des concepts de FRITH de 1992. Nous avons retrouvé notamment deux articles de RINALDI et LEFEBVRE de 2014 (196) et 2016 (197) qui évoquent un tel modèle.…”
Section: ) Le Concept D'action Orientée Vers Un Butunclassified